Seeking general principles in the design of defense systems against hydrogen peroxide - Selvaggio, Gianluca (2017)
Reactive oxygen species (ROS) such as hydrogen peroxide (H2O2), are now known to play critical roles in signal transduction and in coordinating key cellular processes. However, these species can also covalently damage macromolecules and originate other even more deleterious compounds. At the core of this twine between signaling and defense lays the Peroxiredoxin Thioredoxin Thioredoxin Reductase (PTTR) system. Experimental studies of the PTTRS highlighted many commonalities among different types of cells and organisms, but also intriguing differences in cells’ responses to hydrogen peroxide. The current work aims to study the PTTR system and its characteristics. Using a minimal mathematical model, we seek to uncover the general principles of how organisms exploit the properties of ROS for regulation of other protein while avoiding their deleterious effects. These principles, in the form of relationships among rate constants and species concentrations, are thoroughly supported by experimental observations in a variety of organisms and allow to correlate proteins abundance patterns with the modes of response. Depending on the relative abundances of peroxiredoxins, sulfiredoxin, thioredoxin, thioredoxin reductase and alternative H2O2-consuming proteins, the system is capable of distinct responses to changing hydrogen peroxide supplies, including proportional, ultrasensitive, and hysteretic (toggle switch) ones. The complete characterization of the system however requires the definitions of the operative conditions in which the organism lives. A major and so far not univocally defined value is the maximum attained hydrogen peroxide concentration in vivo. To address this problem were developed a series of sensor with different thresholds and capable of memory functions. The peroxide classifier was then used in an inflammation animal model to measure the maximum attained concentrations. The mathematical model developed in this system and the studies of the general principles underlying the PTTR system together with the experimental application of the H2O2 classifier could be used in clinical research or drug development.